BOOSTING FINANCIAL LITERACY IN PRIMARY SCHOOL: A STUDY OF PARTICIPATORY METHODS AND DIGITAL EVALUATION IN INDONESIAN CITIZEN EDUCATION CENTERS, KLANG, SELANGOR, MALAYSIA - Auria Dianing Cahya; Sri Luayyi; Taufik Akbar (LPPM Institut Pendidikan Nusantara Global, 2025)
This community service initiative addressed the challenge of limited access to financial literacy among elementary school children of Indonesian migrant workers in Klang, Selangor, Malaysia. The program aimed to enhance students’ ability to manage money from an early age by introducing practical, contextual, and engaging learning approaches. A participatory method was employed, where students actively engaged in activities supported by worksheets and digital quizzes designed to fit their cognitive stage. Data were gathered through documentation and interactive assessments, with descriptive quantitative analysis used to evaluate outcomes. The findings showed that students significantly improved in distinguishing needs from wants, developing simple budgets, and allocating pocket money for savings. The integration of digital tools increased their motivation and knowledge retention, while participatory activities fostered responsible financial behavior. Overall, the program effectively enhanced children’s basic financial management skills and highlighted the importance of early financial literacy education in non-formal learning environments. These results suggest that participatory and technology-based approaches can serve as innovative models for financial education in disadvantaged communities.